The Synergy of School and Parent: A Strategy to Improve the Quality of Educational Services - SALAFUDIN, MOH ANWAR; Umi Bariroh; Auliya Fahma; Khairu Ramadhani Nurul Hidayah; Faiz Abdul Majid Assharofi (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2025)
This study aims to evaluate the level of parental satisfaction with the educational services at SDIT Kartika Buana and to formulate strategies for improving service quality through a synergistic approach between the school and parents. The research employed a quantitative descriptive method using the Importance-Performance Analysis (IPA) approach. The sample consisted of 50 respondents randomly selected from a population of 319 students. The research instrument was a Likert-scale questionnaire developed based on the five dimensions of service quality as defined by Kotler and Armstrong, as well as Zeithaml and Bitner, namely: tangibles, reliability, responsiveness, assurance, and empathy. The findings indicate an average satisfaction level of 3.93 and an expectation level of 4.20, resulting in a conformity level of 95%. The Cartesian analysis revealed that the quality of the learning program, teacher competence, and the alignment between cost and educational quality are key priorities for improvement. Meanwhile, teacher behavior and the Tahfidz (Qur’an memorization) program fall under the category of aspects that should be maintained. This study highlights that synergy between the school and parents is a critical strategy in maintaining and enhancing the quality of educational services, particularly within integrated Islamic elementary education institutions.